PELAKSANAAN TUGAS WAITER DI SWISS-CAFÉ RESTAURANT HOTEL SWISS-BELINN KARAWANG - Yoel Harianja; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Execution of tasks is a way or stages so that the implementation of work is easy and smooth. In a hotel it is very important to pay attention to the procedures for carrying out the waiter's duties to be carried out. This study aims to find out how important the attention of hotel management is in carrying out the duties of waiters, preparing restaurants, receiving guests, delivering guests, presenting food and drink lists, serving guests, recording guest complaints and any obstacles experienced by waiters when carrying out their duties. taken from Mertayasa's book source (2012) in the Food & Beverage Service section of the Swiss-Belinn Hotel Karawang department. Data collected using interview techniques, observation and documentation. Based on the research that was obtained from the results of the interviews that the implementation of the waiter's duties at the Swiss-café restaurant Hotel Swiss-Belinn Karawang can be said to be quite good because some have followed the procedures and some are still not in accordance with the procedures that have been determined. Keywords: Implementation, Waiter, Swiss-Café Restaurant, Hotel Swiss-Belinn Karawang.